The Melanoma Patient Exchange: Insights from a Supportive Group Intervention for Melanoma Patients and their Caregivers. Issue 1 (2nd January 2019) - Lazor, Tanya; Rinaldo, Emma; Cyr, Annette; Degeer, Ian
ABSTRACT: Melanoma is one of the fastest growing cancers worldwide, and the psychosocial impact of its diagnosis and treatment can be substantial. The authors implemented a support group for melanoma patients and caregivers to address a gap in support services. The authors describe insights from the first year of the program, including group format and dynamics, participant feedback, and satisfaction. Feedback was collected using the Group Session Rating Scale and two open-ended questions. Sixty-six members participated and responses demonstrated high satisfaction with the group (Mean = 38.7/40.0). Similar organizations may utilize these strategies to provide a support group option for their population of interest.